Diagnostic Accuracy of Optic Nerve Ultrasonography and Ophthalmoscopy in Prediction of Elevated Intracranial Pressure - Keihan Golshani; Mehdi Ebrahim zadeh; Ziba Farajzadegan; Fariborz Khorvash (Archives of Academic Emergency Medicine, 2018)
Introduction: Elevated intracranial pressure (ICP) is a major and potentially lethal disorder in patients admitted to the emergency department (ED). Several methods are being used to investigate for elevated ICP. Here we assessed and compared the diagnostic accuracy of two existing tools of ophthalmoscopy and optic nerve ultrasonography in detection of elevated ICP. Methods: 131 participants with probable elevation of ICP referred to the emergency department of Al-Zahra Hospital, Isfahan, Iran, from 2012 to 2014, were enrolled. Brain computed tomography (CT) scan, ultrasonography of optic nerve sheath, and ophthalmoscopy were performed for them. The optic nerves sheath with diameter more than 5 millimeters was considered as elevated ICP. Widening of optic nerve, ocular venous engorgement, blurring, hemorrhage over optic disk, elevation of optic disk, and retinal venous tortuosity were recorded as evidences of ICP rising in ophthalmoscopy. Diagnostic accuracy of the two tools in prediction of ICP rising were compared with the results of brain CT scan as a gold standard. Results: The mean age of participants was 46.29 ± 10 years (77% male). The number of diagnosed elevated ICPs with ophthalmoscopy and ultrasound were 98 (74.8%) and 102 (77.9%) cases, respectively. The calculated sensitivity and specificity of ophthalmoscopy and ultrasonography in detection of ICP rising were 100.0% (95% CI: 88.6-100.0) and 35.4% (95% CI: 26.0-46.2), 100.0% (95% CI: 84.0-100.0) and 31.9% (95% CI: 23.0-41.7), respectively. Conclusion: The present study reveals that bedside ultrasonography of optic nerve sheath and ophthalmoscopy have enough accuracy for screening of patients with probable elevation of ICP. Of course, it should be considered that despite of high sensitivity of both tools, their specificity is low.